A Haptoglobin Exon Copy Number Variant Associates With HIV-Associated Neurocognitive Impairment in European and African-Descent Populations - Bai, Haimeng; Kaur, Harpreet; Kallianpur, Asha R.; Hulgan, Todd; Franklin, Donald R.; Letendre, Scott L.; Ellis, Ronald J.; Bush, William S. (Frontiers in Genetics, 2021)
A common two-exon deletion distinguishes the gene encoding the free hemoglobin capturing protein–haptoglobin (HP)–into two alleles: HP1 and HP2. To evaluate the impact of this copy number variant (CNV) on neurocognitive impairment (NCI) in people living with HIV, we imputed this variant in 432 European-descent (EUR) and 491 African-descent (AFR) participants from the CNS HIV Anti-Retroviral Therapy Effects Research Study using an optimized imputation pipeline and evaluated its associations with NCI. At baseline, in AFR, the HP2 allele decreases the odds of NCI (defined by a global deficit score, GDS, ⩾ 0.5; Odds Ratio, OR = 0.584, p = 0.022). However, in EUR, HP2 increased the odds (OR = 2.081, p = 0.040) of NCI suggesting a detrimental effect. These effects are extended to longitudinal analyses using repeated measurements where the protective effect of the HP2 allele in AFR became marginally significant (p = 0.054) and in EUR the detrimental effect increased in significance (p = 0.037). In EUR, the HP2 allele slightly reduces the risk of NCI over time (OR = 0.028 per allele per year, p = 0.024). Further analyses of cognitive domain-specific impairment revealed that the HP-NCI effect was based on changes in learning, speed of information processing, and verbal domains over time differing by ancestry groups. Overall, these findings suggest that these functional HP CNV alleles influence the likelihood of NCI and contribute to changes in neurocognitive function over time in people with HIV.